Kontribusi Dampak Disiplin Kerja dan Kemampuan Kerja Terhadap Kinerja Pegawai - Makatita, Muhajir (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2020)
Abstract This study aims to study and analyze the influence of work discipline style and work ability on the performance of civil service police officers in Central Maluku Regency, Maluku Province. The survey data collection used a questionnaire instrument with a total sample of 79 employees using census techniques. The results of testing using multiple linear regression analysis techniques show that; work discipline and work ability proved to have a positive and significant effect on the performance of employees of the Civil Service Police Unit of Central Maluku Regency, Maluku Province. This means that the drive to increase work discipline and work ability will trigger an increase in the performance of employees of the Civil Service Police Unit of Central Maluku Regency, Maluku Province. Keywords : Work Discipline, Work Ability, Performance